Static work of scaffolding loaded by actual and standards driven wind forces - Paulina Jamińska (Budownictwo i Architektura, 2014)
This paper presents static analyzes of scaffolding loaded by wind according to Eurocode recommendations and on the basis of computer simulations of air flow around a rectangular building with a scaffolding assembled at one of the walls. On the basis of calculations performed for the scaffold at different angles of wind attack, the maximum values of the stress in the vertical elements of the framework and in the braces are showed, as well as axial forces in the anchors. In addition, critical buckling load analyses were also performed. The comparison indicates that the forces coming from the actual wind loads differ significantly in direction, sense and magnitude from the forces prescribed in the standards. Underestimated wind load can lead to the state of exceeded capacity in scaffolding elements, and consequently to the construction disaster.